2015
DOI: 10.1371/journal.pcbi.1004210
|View full text |Cite
|
Sign up to set email alerts
|

Particle Simulation of Oxidation Induced Band 3 Clustering in Human Erythrocytes

Abstract: Oxidative stress mediated clustering of membrane protein band 3 plays an essential role in the clearance of damaged and aged red blood cells (RBCs) from the circulation. While a number of previous experimental studies have observed changes in band 3 distribution after oxidative treatment, the details of how these clusters are formed and how their properties change under different conditions have remained poorly understood. To address these issues, a framework that enables the simultaneous monitoring of the tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 70 publications
3
21
0
Order By: Relevance
“…These predictions were later supported experimentally [29][30]. Recently, we built a multi-algorithm simulation model of erythrocyte band 3 membrane cluster formation with Spatiocyte [31]. The model showed that strong affinity between the clustering molecules and irreversibly binding hemichromes aid the generation of oxidation induced clusters as observed in experiments.…”
Section: Case Studiessupporting
confidence: 57%
“…These predictions were later supported experimentally [29][30]. Recently, we built a multi-algorithm simulation model of erythrocyte band 3 membrane cluster formation with Spatiocyte [31]. The model showed that strong affinity between the clustering molecules and irreversibly binding hemichromes aid the generation of oxidation induced clusters as observed in experiments.…”
Section: Case Studiessupporting
confidence: 57%
“…5b–d ). Oxidative stress impairs erythrocyte membrane integrity through initial oxidation of hemoglobin, leading to the precipitation of Heinz bodies and band 3 (a major erythrocyte membrane protein) clustering; thus, band 3 clustering serves as an essential molecular marker of erythrocyte removal 40 . Using erythrocytes isolated from 9 to 11 individual whole blood samples, we confirmed that band 3 protein is aggregated with either chloroquine (CQ) or diamide treatment, which was alleviated by AG1 treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been successfully used to capture the influence of microscopic effects on the behavior of cells at the macroscopic scale. These include the formation of a high density ring over the entire bacterium cell membrane as a result of transient membrane association and rebinding of proteins [57], the clustering of proteins on the red blood cell membrane from oxidative stress [62] and the oligomerization of receptors and its influence on ligand binding kinetics [86]. As the spatiotemporal resolution of imaging techniques continue to advance [87], time-dependent reaction kinetics and molecular trajectories will become more accessible.…”
Section: Discussionmentioning
confidence: 99%
“…The run time of Spatiocyte is also comparable to Smoldyn in the benchmark enzymatic reaction model [56]. The reduced computational cost and the simplicity of MLM implementation have promoted its applications in both biological [57][58][59][60][61][62] and chemical [63][64][65] surface reactions. Nonetheless, biological surfaces such the cell and nuclear membranes are not arranged as fixed lattice structures.…”
Section: Introductionmentioning
confidence: 99%